IDENTIFYING THE CONCEPT OF BILINGUALISM AND BILINGUALS THROUGH SEVEN BAKER’S DIMENSIONS OF BILINGUALISM - Mulyani Mulyani (Universitas Islam Negeri Banda Aceh, 2017)
The study is mainly aimed at investigating and analyzing the concept of bilingualism and bilinguals based on seven Baker’s (2011) dimensions of bilingualism; ability, culture, context, age, use, elective bilingualism, and balance of two languages. All of the dimensions were discussed specifically and comparatively based on Baker’s bilingualism dimensions related to the experience of learning second language (L2) of both the participants. However, another dimension; development is not discussed in this study since there is insufficient information and no correlation to the participants’ experience in learning L2. There were two participants involved in this study; they are Australian but coming from different backgrounds and experiences of learning L2. The data was collected by means of semi-structured interviews using both closed-question and open-question methods. The findings indicates that it is arduous to specify to what extent the concept of bilingualism and bilinguals are.